A Thousand Plateaus: Capitalism and Schizophrenia - Deleuze, Gilles 1925-1995; Guattari, Félix 1930-1992 (London Continuum, 2004)
A rare and remarkable book. Times Literary Supplement Gilles Deleuze (1925-1995) was Professor of Philosophy at the University of Paris VIII. He is a key figure in poststructuralism, and one of the most influential philosophers of the twentieth century. Félix Guattari (1930-1992) was a psychoanalyst at the la Borde Clinic, as well as being a major social theorist and radical activist. A Thousand Plateaus is part of Deleuze and Guattaris landmark philosophical project, Capitalism and Schizophrenia a project that still sets the terms of contemporary philosophical debate. A Thousand Plateaus provides a compelling analysis of social phenomena and offers fresh alternatives for thinking about philosophy and culture. Its radical perspective provides a toolbox for nomadic thought and has had a galvanizing influence on todays anti-capitalist movement. Translated by Brian Massumi>--This text refers to an out of print or unavailable edition of this title.